CURRENT TRENDS IN UNDERGRADUATE MEDICAL AND DENTAL RESEARCH: A PICTURE FROM PAKISTAN - Jeelani, Waqar; Aslam, Sanaa Masood; Elahi, Asrar (Journal of Ayub Medical College Abbottabad, 2014)
Background: Initiatives taken over the last few years have led us to the day when most of the medical and dental institutions in the developed countries have established a strong research culture at undergraduate level but the situation is quite the contrary in Pakistan. This study was carried out to investigate the current trends in undergraduate medical and dental research and to highlight the research barriers. Methods: A cross-sectional study was conducted at six medical and dental colleges of Rawalpindi and Islamabad. A structured questionnaire was used to collect data from 300 students. Results were recorded as percentages. Findings of current survey were compared with those of already reported in literature using chi-square test. Results: Out of 300 students, 206 (68.7%) students had already participated in research as principal researcher, co-researcher or as a research volunteer. Internet was most effective method of publicity of research opportunities reported by 74% of students. Only 36.7% students reported the presence of student research office at their institute. Accessibility to medical and dental journals and availability of research funds were reported by 77.2% and 13.4% of students, respectively. Lack of funding and academic overload were two main research barriers reported by 92.6% and 91.9% of students, respectively. Conclusion: The fraction of medical and dental students who are confident that they can plan, conduct and write a research study has increased over last four years. There is an improvement in the availability of research promoting activities but the number of research barriers is still high. Keywords: Biomedical research, Undergraduate, Medical, Education